After all, what's Selection by Consequences? - Monalisa de Fátima Freitas Carneiro Leão; Marcus Bentes Carvalho Neto (Interação em Psicologia, 2017)
The Skinner's proposal entitled 'Selection by Consequences' seems to ensure a commitment to selectionist epistemology. This notion, however, lacks a consensual definition in the area. The aim of this article is to propose a conceptualization of Skinnerian proposal. We have examined such explanatory proposal through an analysis of the main Skinnerian texts on the subject, in order to delimit the sufficient and defining aspects of this scientific proposal. We have concluded that 'selection by consequences' can be defined as a causal mode based on a probabilistic interdependence relationship between events, which explains the origin and evolution of behavioral phenomena as product of three histories of variation and selection: phylogenetic, ontogenetic and cultural.